Endocrine system after 2 years of COVID-19 vaccines: A narrative review of the literature - Pezzaioli, Letizia Chiara; Gatta, Elisa; Bambini, Francesca; Facondo, Paolo; Gava, Maria; Cavadini, Maria; Buoso, Caterina; Di Lodovico, Elena; Rotondi, Mario; Ferlin, Alberto; Cappelli, Carlo (Frontiers in Endocrinology, 2022)
Purpose To describe the current knowledge on the potential endocrine adverse effects post COVID-19 vaccines. Methods A PubMed/MEDLINE, Web of Science, and Scopus research was performed. Case reports, case series, original studies and reviews written in English and published online up to 31st July 2022 were selected and reviewed. The final reference list was defined based on the relevance of each paper to the scope of this review. Results The available data showed that endocrine side effects are generally rare and with favorable outcome, being thyroid disorders the most common. Conversely, data on type 1 diabetes mellitus are rare, adrenal and pituitary events are even anecdotal. Finally, the available clinical studies suggest no impact on female reproductive system and on male and couple fertility. Conclusion Overall, these data show that after two years of COVID-19 vaccines the endocrine system is not heavily threatened.